Measuring political will: An index of commitment to disaster risk reduction. (March 2019) - Lassa, Jonatan A.; Surjan, Akhilesh; Caballero-Anthony, Mely; Fisher, Rohan
Abstract: The future of societal resilience depends largely on political commitment to allocate resources to manage and reduce disaster risks and vulnerabilities and build resilience. Lack of political commitment has often been cited as one of the culprits inhibiting countries to prioritise actions towards mitigating hazards and reducing risks in short and long term. While acknowledging existing global disaster risk assessments such as World Risk Report, Climate Risk Index, and Global Assessment Report on DRR, etc., we advocate for a new index with the intention to trigger critical discussion that drive political commitment for disaster risk reduction worldwide. Under the aegis of 2030 global targets of meeting the Sustainable Development Goals and Sendai Framework for Disaster Risk Reduction, governments should work collaboratively to substantially reduce global disaster mortality and mitigate loss and damage of economic assets and infrastructures. With this in mind, this paper proposes an index aimed at measuring countries' commitment to reduce risks from disasters and changing climate. Commitments from nations can vary and may include: investment in early warning systems; disaster vulnerability reduction activities such as fiscal allocation for mitigation, raising awareness, promotion and incentives for stakeholders to participate in managing risks. This paper contributes to new knowledge and understanding on how political will can be assessed and monitored. It contributes to both local and global debates to strengthen institutional mechanism by way of fostering political will for building resilience and reducing vulnerabilities.